The Effects of Hatha Yoga and Specific Balance Exercises in Older Adults Living in Nursing Homes - Selenia di Fronso; Luca Tamburrino; Maurizio Bertollo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
We tested the effects of Hatha Yoga and specific balance exercises on balance function and fear of falling in older adults living in nursing homes. Twenty-six older adults underwent either Hatha Yoga or simple balance exercises practice. Before, during, and after completing the two programmes, the performance-oriented mobility assess- ment tool and the Italian version of the falls efficacy scale international were administered to assess participants' balance function and fear of falling. Hatha Yoga practice yielded significant differences in balance function and fear of falling associated with low falls risk and reduced fear of falling. Specific balance exercises practice yielded significant differences only on balance function but with reduced performance-oriented mobility assessment tool scores associated with a greater falls risk. Accordingly, to improve the quality of life of older adults living in nursing homes, the practice of Hatha Yoga should be encouraged.